AN ANALYSIS OF STUDENTS’ ERRORS IN USING QUANTIFIERS OF THE FIRST SEMESTER AT INSTITUTE AGAMA ISLAM AL-AZHAAR LUBUK LINGGAU - Novita Sari (Edu-Ling: Journal of English Education and Linguistics, 2020)
This research aimed at finding out the types of students’ error in using quantifiers and to finding out the causes of students’ error in using quantifiers made by the students of first semester at Institute Agama Islam (IAI) Al-Azhaar Lubuklinggau. The design of this researchwas descriptive. The subjects were the students of first semester at Institute Agama Islam Al-Azhaar Lubuklinggau who attended English subject at Tarbiyah faculty with total of 31 students. The instruments were list of types of errors and list of causes of errors. The reseacher focused the study on using countable noun and uncountable noun. The findings revealed that there were 165 errors found in using quantifiers made by the students. The errors were classified into six quantifiers, namely, “much”, “many”, “a few”, “a little”, “a number”, and “amount”. with the most dominant error was in using “a few”. Moreover, there were three causes of quantifier errors, namely; carelessness, first language, and translation. However, the dominant cause was translation. Another causes of errors were lack of vocabulary and lack of grammar. It can be concluded that the most dominant type of quantifiers error made by the students was in using ‘a few’ which is caused by the students’ inability to find the suitable word in their writing.